GATA3 Promotes the Neural Progenitor State but Not Neurogenesis in 3D Traumatic Injury Model of Primary Human Cortical Astrocytes - Celikkaya, Hilal; Cosacak, Mehmet Ilyas; Papadimitriou, Christos; Popova, Stanislava; Bhattarai, Prabesh; Biswas, Srijeeta Nag; Siddiqui, Tohid; Wistorf, Sabrina; Nevado-Alcalde, Isabel; Naumann, Lisa; Mashkaryan, Violeta; Brandt, Kerstin; et al. (Frontiers in Cellular Neuroscience, 2019)
Astrocytes are an abundant cell type in the vertebrate central nervous system and can act as neural stem cells in specialized niches where they constitutively generate new neurons. Outside the stem cell niches, however, these glial cells are not neurogenic. Although injuries in the mammalian central nervous system lead to profound proliferation of astrocytes, which cluster at the lesion site to form a gliotic scar, neurogenesis does not take place. Therefore, a plausible regenerative therapeutic option is to coax the endogenous reactive astrocytes to a pre-neurogenic progenitor state and use them as an endogenous reservoir for repair. However, little is known on the mechanisms that promote the neural progenitor state after injuries in humans. Gata3 was previously found to be a mechanism that zebrafish brain uses to injury-dependent induction of neural progenitors. However, the effects of GATA3 in human astrocytes after injury are not known. Therefore, in this report, we investigated how overexpression of GATA3 in primary human astrocytes would affect the neurogenic potential before and after injury in 2D and 3D cultures. We found that primary human astrocytes are unable to induce GATA3 after injury. Lentivirus-mediated overexpression of GATA3 significantly increased the number of GFAP/SOX2 double positive astrocytes and expression of pro-neural factor ASCL1, but failed to induce neurogenesis, suggesting that GATA3 is required for enhancing the neurogenic potential of primary human astrocytes and is not sufficient to induce neurogenesis alone.